Armadillos and leprosy: from infection to biological model - Ilanna Vanessa Pristo de Medeiros Oliveira; Patrícia Duarte Deps; João Marcelo Azevedo de Paula Antunes (Revista do Instituto de Medicina Tropical de São Paulo)
ABSTRACT Mycobacterium leprae is the primary causative agent of Hansen’s disease or leprosy. Besides human beings, natural infection has been described in animals such as mangabey monkeys and armadillos. Leprosy is considered a global health problem and its complete pathogenesis is still unknown. As M. leprae does not grow in artificial media, armadillos have become the primary experimental model for leprosy, mimicking human disease including involvement of the peripheral nervous system. Leprosy transmission occurs through continuous and close contact of susceptible people with untreated infected people. However, unknown leprosy contact has been reported in leprosy-affected people, and contact with armadillos is a risk factor for leprosy. In the USA, leprosy is considered a zoonosis and this classification has recently been accepted in Brazil. This review presents information regarding the role of wild armadillos as a source of M. leprae for human infections, as well as the pathogenesis of leprosy.